2015
DOI: 10.1021/acs.biochem.5b00256
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Functional Analyses of the Lectin Domain of Glucosidase II: Insights into Oligomannose Recognition

Abstract: N-Glycans are modified as part of a quality control mechanism during glycoprotein folding in the endoplasmic reticulum (ER). Glucosidase II (GII) plays a critical role by generating monoglucosylated glycans that are recognized by lectin chaperones, calnexin and calreticulin. To understand how the hydrolytic activity of GIIα is enhanced by the mannose 6-phosphate receptor (MPR) homology domain (MRH domain) of its β subunit, we now report a 1.6 Å resolution crystal structure of the MRH domain of GIIβ bound to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…The differences in the activity of the enzyme against glycoproteins carrying a variable number of N-linked glycans have led to the suggestion that more than one glycan is needed for α-GluII to allow entry of a glycoprotein into the calnexin/calreticulin cycle (29). In this case, the mannose 6-phosphate receptor homology (M6PRH) C-terminal domain of the β-subunit would bind a terminal α(1,2)-linked mannose residue on one N-linked glycan (30,31), helping the recruitment of the other N-linked glycan to the active site (29,32). The shape and dimensions of our Mmα-GluII SAXS envelope and Mmα-GluII Tryps crystal structure are compatible with a role for the M6PRH C-terminal domain of the β-subunit assisting glucose hydrolysis by binding a second glycan on glycoproteins carrying more than one glycan (29,32).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The differences in the activity of the enzyme against glycoproteins carrying a variable number of N-linked glycans have led to the suggestion that more than one glycan is needed for α-GluII to allow entry of a glycoprotein into the calnexin/calreticulin cycle (29). In this case, the mannose 6-phosphate receptor homology (M6PRH) C-terminal domain of the β-subunit would bind a terminal α(1,2)-linked mannose residue on one N-linked glycan (30,31), helping the recruitment of the other N-linked glycan to the active site (29,32). The shape and dimensions of our Mmα-GluII SAXS envelope and Mmα-GluII Tryps crystal structure are compatible with a role for the M6PRH C-terminal domain of the β-subunit assisting glucose hydrolysis by binding a second glycan on glycoproteins carrying more than one glycan (29,32).…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the mannose 6-phosphate receptor homology (M6PRH) C-terminal domain of the β-subunit would bind a terminal α(1,2)-linked mannose residue on one N-linked glycan (30,31), helping the recruitment of the other N-linked glycan to the active site (29,32). The shape and dimensions of our Mmα-GluII SAXS envelope and Mmα-GluII Tryps crystal structure are compatible with a role for the M6PRH C-terminal domain of the β-subunit assisting glucose hydrolysis by binding a second glycan on glycoproteins carrying more than one glycan (29,32). In the absence of the β-subunit, α-GluII activity is reduced in vivo (27) and in vitro (33) to about 5-10% of wt levels and the recombinant α-subunit is unstable unless associated with the β-subunit (4, 28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this microorganism, we have successfully determined crystal structures of enzymes involved in ER quality control, including GIIα . It has been confirmed that closely related species, such as Aspergillus oryzae and Schizosaccharomyces pombe, have enzymatically active GII with the same substrate specificity as that of the mammalian counterparts . These results encouraged us to perform a structural study of GIIβ derived from C. thermophilum .…”
Section: Resultsmentioning
confidence: 79%
“…Mutations in GANAB and PRKCSH encoding GIIα and GIIβ cause autosomal‐dominant polycystic kidney and liver diseases (ADPKD and ADPLD) . To date, the 3D structures of GIIα and the MRH domain of GIIβ have been determined . However, structural information of GIIβ G B as well as its mode of interaction with GIIα has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%